Chronic toxicity of sulfate to adult tellinid bivalve Macoma balthica in brackish water - Sarathchandra, Hansika (2024)
Sulfate is a naturally occurring compound found in water bodies. Estuarine brackish water, such as that in the Baltic Sea in northern Europe, contains 100-500 mg/L of sulfate. However, excessive levels of sulfate due to various anthropogenic activities could increase water salinity and negatively impact aquatic life. There is a scarcity of chronic toxicity data on sulfate for performing a Species Sensitivity Distribution (SSD) analysis and setting Water Quality Guidelines (WQGs) for brackish water. To address this gap, this study focused on the bivalve species Macoma balthica commonly found in brackish water, to evaluate the chronic toxicity of sulfate and enhance the data availability for SSD analysis in brackish water. M. balthica holds a crucial position in the ecosystem dynamics of the northern Baltic Sea, with no other species capable of completely assuming its vital ecological roles. The primary aim of this study was to investigate the effective concentrations of sulfate to adult M. balthica in brackish water and to enhance the availability of chronic toxicity data for SSD analysis in brackish water. In this chronic toxicity test, the effective concentrations of sulfate were determined by exposing adult M. balthica to varying sulfate concentrations ranging from 500 mg/L to 11500 mg/L for 28 days in a controlled laboratory environment. Key endpoints measured included foot or siphon movement rate, activity frequency, wet and dry weights of soft tissues, and length. M. balthica tolerated higher sulfate concentrations than freshwater mussels with a chronic effective concentration (EC10) at 2291 mg/L. The excessive sulfate levels significantly decreased the activity frequency and foot or siphon movement rate of M. balthica in brackish water.